First Draft Genome of the Sable, Martes zibellina. (14th February 2020) - Liu, Guangshuai; Zhao, Chao; Xu, Dongming; Zhang, Huanxin; Monakhov, Vladimir; Shang, Shuai; Gao, Xiaodong; Sha, Weilai; Ma, Jianzhang; Zhang, Wei; Tang, Xuexi; Li, Bo; et al.
Abstract: Members of genus Martes provide early warning signals about forest ecosystem health and are designated as a Management Indicator Species. As one of the most widespread members in Martes, the sable ( Martes zibellina ) is a circumboreal small predator found throughout all taiga zoogeographical zones of Eurasia and shows distinct population differentiation and morphological variations. To support further studies on striking local adaptation and population evolution, we present the first sable genome, assembled de novo from an individual originating in the Great Khingan Mountains (China). The assembled genome is 2.42 Gb, consisting of 15, 814 scaffolds with a scaffold N50 of 5.20 Mb. Searches for complete Mammalia BUSCO (Benchmarking Universal Single-Copy Ortholog) gene groups found that 95.15% of the curated single-copy orthologs were assembled as complete, suggesting a high level of completeness of the genome. We totally predicted 19, 413 protein-coding genes, and 0.82 Gb of repeat sequences was annotated. We also detected 1, 257 olfactory receptor genes and found more functional olfactory receptor genes in sable than in other Mustelidae species, which provide a possible genetic explanation for the acute sense of smell of the sable for searching the preys under deep snow. Phylogenetic analyses revealed that the ferret ( Mustela putorius furo ) and sea otter ( Enhydra lutris ) form a clade that is sister to the sable, which was dated ∼16.4 Ma. Overall, our study provided the first reference genome for research in a broad range of areas including local adaptations, population evolution, conservation, and management for sable.